EVALUATION OF INTERCONNECTIVITY BETWEEN HIGHER EDUCATION AND BUSINESS – BULGARIAN CASE - BERBEROVA-VALCHEVA, Tzvetelina; PETROV, Kamen; TSONKOV, Nikolay (Journal of European Economy, 2022)
This article is dedicated to the problems identified by the Bulgarian business in terms of staff with higher education. In practice, businesses believe that research and educational institutions must provide an educational service that corresponds to their requirements for the level of competencies. The paper investigates the industries and sub-industries where the need for staff is most urgent. The model of more general education is embedded in the new global realities, which largely means that universities offer educational services of a more general nature. In this situation, it is difficult to overcome the divide between knowledge and skills of graduates and business requirements. This fact shows the objective gap between students’ preparation for workforce and business expectations. The authors also study the provision of educational services in the real sector, in particular the opinion of employers regarding the strength of young professionals outside the educational environment. Thus, there is a need to determine connections in the different areas of the labour market, e.g., business, services and production, to higher education. Analysis of the trends and conditions in the selection of specialists with higher education is an important aspect here. The authors believe that a flexible and adaptive economic environment is needed, which is focused on the global and regional peculiarities of territorial development and available human capital. JEL: I23, I25, M5, P46, R23.